Effects of a More Restrictive Transfusion Trigger in Trauma Patients. Issue 4 (April 2019) - Garland-Kledzik, Mary; Gaffley, Michaela; Crouse, David; Conrad, Collin; Miller, Preston; Martin, R. Shayn
Since the Transfusion Requirements in Critical Care trial, studies have shown that acutely ill patients can drift as a low as 5 g/dL. This study reviews a transfusion trigger change to 6.5 g/dL, which we hypothesize will conserve resources and improve quality of care. This is a retrospective chart review at an urban Level I trauma center from January through December 2015 after our trauma service changed the transfusion trigger from 7 to 6.5 g/dL. Outcomes in patients before (TT7) and after (TT6.5) the change in transfusion threshold were then compared. One hundred thirty-one discrete patients were included in this trial, with 285 instances of a hemoglobin of 7 g/dL or less and 178 transfusions. Seventy-two patients were before the change in threshold and 59 after. There was no change in length of hospital stay, ICU stay, ventilator days, mortality, and organ system failure after change in the transfusion threshold. After initiation of a more conservative threshold, 72 units of blood were saved. Decreased transfusion threshold was associated with no worse outcomes associated with decreased resource utilization.